The Genetic Polymorphisms of NLRP3 Inflammasome Associated with T Helper Cells in Patients with Multiple Myeloma - Xueyun Zhao; Mingqiang Hua; Shuxin Yan; Jie Yu; Fengjiao Han; Chaoqin Zhong; Ruiqing Wang; Chen Zhang; Ming Hou; Daoxin Ma (Journal of Immunology Research)
The pathogenesis of multiple myeloma (MM) remains unclear and the NLRP3 inflammasome has been more and more recognized in the progression of many diseases. To investigate the role of the NLRP3 inflammasome in MM, we determined the genetic polymorphisms and expression of NLRP3 inflammasome-related genes (IL-1β, IL-18, CARD8, and NF-κB) in MM patients, and explored their clinical relevance. Furthermore, we investigated the relationship of the NLRP3 inflammasome with Th cells in MM. Our study showed that the CARD8-C10X (rs2043211) AT genotype contributed to the susceptibility of MM. CARD8-C10X TT patients had earlier clinical stage. The WBC count in the three CARD8 genotypes showed an increasing trend (AA<AT<TT). Compared with patients with NF-κB-94 ins/del ATTG ins/ins and ins/del, patients with del/del had the highest myeloma cell ratio. Patients with IL-18 (rs16944) TT had the highest hemoglobin concentration (GG<GT<TT). Furthermore, we found that the genotype of CARD8-C10X (rs2043211) or NF-κB-94 ins/del ATTG was closely related to the frequency of Th1. Therefore, the genetic polymorphisms of the NLRP3 inflammasome associated with Th cells might be involved in the pathogenesis of multiple myeloma.